An Assessment of Asymptomatic Bacteriuria among Women with Vesico-Vaginal Fistula in South-Eastern Nigeria - Adeoye, Ileogben Sunday; Oladeinde, Oladapo; Uneke, Jesse; Adeoye, Julie (Nepal Journal of Epidemiology, 2011)
Objective: Vesico-vaginal fistula (VVF) involves the pathological communication between the urinary bladder and vagina, possible complications arising from urinary tract infection merits consideration. This study seeks to evaluate significant bacteriuria among VVF clients. Setting: The setting was the South east Fistula Centre, Abakaliki, Ebonyi State, Nigeria. Population: This was a total population study of all consenting HIV negative VVF clients. Method: This cross-sectional study assessing asymptomatic bacteriuria was conducted among 109 HIV negative VVF clients using standard microbiological technique. Haematological and anthropometric parameters were also assessed. Results: The prevalence of asymptomatic bacteriuria was 76.1% and the highest prevalence was among clients aged 21-30years (90.3%), those who have had more than seven deliveries (85.0%) and those whose labour duration lasted above 48hours (76.7%). The prevalence of bacteriuria was least among women with VVF for less than a year. The prevalence was highest among patients with intra cervical fistula (83.3%). Bacteriuria prevalence was highest among women of blood group AB (100%). The rate was higher among women whose heights were > 1.53metres and whose weights were < 51kilogram. Six different bacterial species isolated include E. coli (41.0%), Proteus species (21.7%), and Klebsiella species (18.1%). Though the bacterial isolates were resistance to many of the antibiotics assessed, the highest level of resistance was observed with perfloxacin, cotrimoxazole, while the highest level of susceptibility was with Ciprofloxacin. Conclusion: The prevalence of bacteriuria in this study is rather high and should not be neglected in the management of VVF clients. Key Words: Assessment; Asymptomatic Bacteriuria; VVF; Southeast Nigeria. DOI: http://dx.doi.org/10.3126/nje.v1i2.5141 Nepal Journal of Epidemiology 2011;1 (2):64-69